2004
DOI: 10.7326/0003-4819-141-2-200407200-00009
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication: The Relationship between Having a Living Will and Dying in Place

Abstract: Living wills are associated with dying in place rather than in a hospital. This implies that previous research examining only people who died in a hospital suffers from selection bias. During advance care planning, physicians should discuss patients' preferences for location of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 24 publications
2
82
2
3
Order By: Relevance
“…However, despite some evidence regarding improved quality, neither strategy clearly reduces costs for elderly Medicare beneficiaries [4][5][6][7] . Continuity of care has been associated with patients and their families experiencing a "higher quality death" 8 , with fewer emergency department visits for cancer patients 9 , increased patient satisfaction, increased adherence to recommended care, and less duplicate testing [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…However, despite some evidence regarding improved quality, neither strategy clearly reduces costs for elderly Medicare beneficiaries [4][5][6][7] . Continuity of care has been associated with patients and their families experiencing a "higher quality death" 8 , with fewer emergency department visits for cancer patients 9 , increased patient satisfaction, increased adherence to recommended care, and less duplicate testing [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…16 Recently, studies have shown that advance directives are associated with patients receiving less lifesustaining treatment and of dying at home vs. dying in a hospital, 17,18 but it was unclear if these outcomes were consistent with patient wishes. Furthermore, it has never been determined how often patients are placed in a circumstance where advance directives could guide care.…”
Section: Communication and Decision-making At The End Of Lifementioning
confidence: 99%
“…Estudos mais antigos revelaram que os mesmos tinham efeito mínimo nas decisões de impedir ou remover o cuidado [41][42][43][44][45] e pouco contribuíam para aumentar a consistência do cuidado recebido e o desejo do paciente 46 . Estudo mais recente demonstrou que pacientes com DAV estão menos propensos a receber tratamento de suporte de vida ou de morrer no hospital 47 , mas ainda não se tem certeza se os resultados são consistentes com os desejos dos pacientes. Estudo prospectivo concluiu que os desejos previamente expressos eram seguidos em 75% dos casos, independentemente da existência de uma DAV…”
unclassified